Studi Kasus: Penerapan Perioperatif Care Pada Diagnosa Cholelithiasis Dengan Tindakan Operasi Kolesistektomi Laparatomi - Irgi Biantara; Viky Rosita Dewi; Lutfi Nur Kharomah; Gandhes Putri Dwikijayanti; Yunanda Tri Hidayat; Supriyanto Supriyanto (Universitas Muhamadiyah Manado, 2023)
Cholelithiasis or gallstones are pieces of solid material that form in the gallbladder. Gallstone disease or cholelithiasis is often found in various countries, including Indonesia. One of the collaborative actions to overcome the problem of cholelithiasis is cholecytectomy surgery. This case study aims to determine the application of perioperative care in patients with a diagnosis of cholelithiasis by laparotomy for cholecystectomy. The method in this study was a case study in cholelithiasis patients by providing intervention and care at the pre-operative, intra-operative and post-operative stages. The results of this case study indicate that the application of perioperative care by intervening reduces preoperative anxiety, controls bleeding and controls infection during surgery, prevents falls and reduces postoperative pain. It can be concluded that the application of perioperative care as an action performed by operating room nurses as well as surgeons and anesthesiologists in order to prepare patients for surgery with the aim of ensuring intraoperative patient safety. For health workers, both doctors and nurses, they always provide education related to a healthy lifestyle. Nurses monitor perioperative patients, educate patients and provide nursing care. In addition, it also informs the team about changes in patient status, and evaluates post-surgery.